The Funambulist Pamphlets 8: Arakawa + Madeline Gins (2014)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist, collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema. Volume 8 is dedicated to The Reversible Destiny Foundation created by Arakawa and Madeline Gins. The Foundation is much more than an architectural practice. It articulates art, philosophy, poetry, architecture and, to some extent, science in a dialogue that benefits each of these disciplines and ultimately serves one of the most radical ideas that apply to architecture: the action of non-dying. Guest authors include Shingo Tsuji, Stanley Shostak, Russell Hughes, and Jean-François Lyotard